ANALYSIS OF THE LEVEL OF WELFARE OF THE FISHERMAN COMMUNITY AT THE VILLAGE FISH LANDING BASE TANJUNG LUAR, EAST LOMBOK - Mulyani, Laily Fitriani; Asri, Yuliana; Dwiyanti, Septiana (Indonesian Journal of Fisheries Community Empowerment (Jurnal Pengabdian Perikanan Indonesia), 2023)
This service aims to determine the level of welfare of fishing communities in East Lombok. This service was carried out for fishermen at the Tanjung Luar Fish Landing Base, East Lombok Regency, West Nusa Tenggara. The sample in this study is 15% of the total fisherman population in the base area. Data collection technique used is interview. The data analysis technique used was descriptive qualitative analysis. The results showed that the welfare level of the fishing community was 52 respondents (54.1%) belonging to the poor, 36 respondents (37.5%) belonging to the prosperous I, and 8 respondents (8.3%) belonging to the prosperous II. If it is related to the 2022 East Lombok Regency Minimum Wage, which is Rp. 2,372,532, then all respondents fall into the poor category, the income of the pre-prosperous people is Rp. 897,000, the prosperous people I Rp. 1,149,000, and the prosperous people II Rp. 1,470,000.